The energy of bianchi type i and II universes in teleparallel gravity - So, Lau Loi; Vargas, T. [UNESP] (My University, 2005)
For certain models, the energy of the universe, which includes the energy of both matter and the gravitational fields, is obtained by using the quasi-local energy-momentum in teleparallel gravity. It is shown that, in the case of the Bianchi type I and II universes, not only the total energy but also the quasi-local energy-momentum for any region vanishes independently of the three dimensionless coupling constants of teleparallel gravity. © 2005 THE PHYSICAL SOCIETY OF THE REPUBLIC OF CHINA.